Pengembangan dan Pelatihan Perpajakan Games Edukasi Perpajakan Untuk Meningkatkan Kesadaran Pajak Early Tax Payer - Asmoro Priandhita Sukowidyanti; Ferina Nurlaily; Edlyn Khurotul Aini (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2019)
The education and socialization of taxation provided early on is a government investment that benefits can be felt in the future. Based on this background, we developed a 3-dimensional tax education game that is used to provide additional knowledge and understanding to elementary school-level children on the importance of taxes so that they can ultimately raise awareness to pay taxes in the future. The method used is to hold discussions with partners, develop 3D educational games applications, carry out training on tax education games, and evaluate the results of training implementation. The training activities were carried out in 3 (three) Elementary Schools namely SD Negeri Experiment 1 Malang SD Negeri Rampal 1 Celaket Malang, and SD Negeri Model Malang. The results of the training showed that tax education games are effective in increasing tax knowledge and awareness. This can be seen from the increase in the quality of understanding related to taxation based on the Pre Test of 79.05% and increased after Post Test to be 86, 62%.